Gut Escherichia coli expressing Pb2+-adsorption protein reduces lead accumulation in grass carp, Ctenopharyngodon idellus. (1st May 2021) - Chen, Xiao; Yang, Jinfeng; Ling, Zhenmin; Zhou, Tuoyu; Zhou, Bojian; Wang, Haoyang; Li, Xiangkai; Liu, Pu
Abstract: Lead (Pb 2+ ) is easy to accumulate in fish which become a major source of Pb 2+ exposure to humans. In this study, a recombinant Escherichia coli strain expressing Pb 2+ -specific surface-binding protein anchored by the ice nucleation protein was introduced into grass carp ( Ctenopharyngodon idellus ) gut to investigate its protective effect against dietary Pb 2+ exposure. Pb 2+ mostly precipitated on the surface of the engineered strain through Pb 2+ -specific surface-binding protein, with a maximum adsorption efficiency of 73% and an adsorption capacity of 163 μmol/g dry cells. The Pb 2+ concentration in engineered bacteria-fed grass carp was reduced significantly, and the residual level of Pb 2+ in feces was increased by 76%, compared with the control group. Meantime, the engineered bacteria were able to mitigate the oxidative stress and histological alterations of intestines and dysbiosis of gut microbiota induced by Pb 2+ exposure. Thus, the engineered bacterium that can effectively reduce Pb 2+ residue in grass carp might be a useful tool for decontamintion of lead in aquatic organisms. Graphical abstract: Image 1 Highlights: A lead-specific adsorption strain E. coli PbBD was constructed. E. coli PbBD effectively reduced Pb 2+ accumulation and helped Pb 2+ excretion in fish. E. coli PbBD helped protecting intestinal health and microbial homeostasis under Pb 2+ stress. E. coli PbBD posed no adverse effect on fish, thus can be a useful lead-removal tool in fish.